CARGO DISTRIBUTING OPTIMIZATION SCHEME FOR AIRFREIGHT SERVICES WITH A STOCHASTIC SIMULATION OF DEMAND - Raihan Putri Nurmawan, Azeilla
The efficiency of transportation and logistics is crucial to the community’s economic sustainability. Airfreight services are one of the most important services in the transportation and logistics industry, especially in Indonesia, which is an archipelago country. To minimize operational cost in airfreight service companies, an optimal cargo distribution scheme needs to be determined to reduce complexity and maximize the use of aircraft capacity. The demand of air cargo served by airfreight services also needs to be generated so that the data remains relevant to the trend of the airfreight industry in Indonesia. This Final Project discusses a stochastic simulation scheme to generate air cargo demand that replicates targeted market shares and represents the trend, including holidays trend. The resulting relative error for generated demand of air cargo is quite reasonable and relatively low. This Final Project also discusses an optimization method for cargo distribution schemes to reduce complexity and maximize the use of aircraft capacity as an initial step in efforts to save operational cost. Based on the assumptions used in this Final Project, the designed distribution scheme can fully reduce the complexity of distribution and optimize the aircraft capacity up to 100 percent for at least 1 city in a complete route. The result of this Final Project will be used in the next research regarding operational costs optimization for airfreight services.